A novel Laennec's capsule tunnel approach for pure laparoscopic left hemihepatectomy: a propensity score matching study - Lai, Jianlin; Wu, Junyi; Bai, Yannan; Tian, Yifeng; Wang, Yaodong; Qiu, Funan (Frontiers in Surgery, 2023)
Background With the development of laparoscopic hepatectomy, there are different surgical approaches and pedicle anatomical methods for laparoscopic left hepatectomy. Combined with our practical experience, we proposed a method of transhepatic Laennec membrane tunnel for laparoscopic left hemihepatectomy (LT-LLH) and investigated the feasibility by comparison with the extrahepatic Glissonian approach for laparoscopic left hemihepatectomy (GA-LLH). Patients and methods The data of patients who underwent laparoscopic left hepatectomy in the Department of Hepatobiliary Pancreatic surgery of Fujian Provincial Hospital from December 2019 to March 2022 were analyzed retrospectively. Among them, 45 cases underwent laparoscopic left hemihepatectomy with an extrahepatic Glissonian approach, and 38 cases underwent laparoscopic left hemihepatectomy via transhepatic Laennec membrane tunnel approach. A 1:1 propensity score matching (PSM) method was performed to compare the perioperative indexes and long-term tumor prognosis between the two groups. Results After 1:1 PSM, 33 patients in each group were selected for further analysis. Compared with the GA-LLH group, the operation time of the LT-LLH group was shorter. There was no significant difference in the incidence of total complications between the two groups. Moreover, no statistical differences were found in disease-free survival and overall survival between the two groups. Conclusion It is safe, faster, and convenient for selective appropriate cases to carry out laparoscopic left hemihepatectomy through the hepatic Laennec membrane tunnel, which is suitable for clinical promotion.